Eficacia del nylon de pescar en esterilización tubaria - García, Jorge (2015)
OBJECTIVE: To show the efficacy of fishing nylon thread were performed to 208 patients. Follow-up was during 2 years. RESULTS: Pregnancy rate 0%. CONCLUSlON: Fishing nylon thread is a adequate suture for voluntary surgical contraception.